2015
DOI: 10.5194/os-11-323-2015
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the anthropogenic tritium transient and its decay product helium-3 in the Mediterranean Sea using a high-resolution regional model

Abstract: Abstract. This numerical study provides the first simulation of the anthropogenic tritium invasion and its decay product helium-3 ( 3 He) in the Mediterranean Sea. The simulation covers the entire tritium ( 3 H) transient generated by the atmospheric nuclear weapons tests performed in the 1950s and early 1960s and is run till 2011. Tritium, helium-3 and their derived age estimates are particularly suitable for studying intermediate and deep-water ventilation and spreading of water masses at intermediate/deep l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 64 publications
4
41
0
Order By: Relevance
“…This model satisfactorily simulates the main structures of the thermohaline circulation of the Mediterranean Sea, with mechanisms having a realistic timescale compared to observations. In particular, tritium/helium-3 simulations (Ayache et al, 2015) have shown that the EMT signal from the Aegean sub-basin is realistically simulated, with its corresponding penetration of tracers into the deep water in early 1995. The strong convection event of winter 2005 and the 968 M Ayache et al: Simulation of the mantle and crustal helium isotope signature following years in the Gulf of Lion was satisfactorily captured as well.…”
Section: Description Of the Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…This model satisfactorily simulates the main structures of the thermohaline circulation of the Mediterranean Sea, with mechanisms having a realistic timescale compared to observations. In particular, tritium/helium-3 simulations (Ayache et al, 2015) have shown that the EMT signal from the Aegean sub-basin is realistically simulated, with its corresponding penetration of tracers into the deep water in early 1995. The strong convection event of winter 2005 and the 968 M Ayache et al: Simulation of the mantle and crustal helium isotope signature following years in the Gulf of Lion was satisfactorily captured as well.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…Physical forcing fields are read daily and interpolated to give values for each 20 min time step. The same approach was used by Ayache et al (2015) to model the anthropogenic tritium invasion and by Palmiéri et al (2015) to simulate CFCs and anthropogenic carbon. This choice is justified by the fact that these tracers are passive.…”
Section: The Tracer Modelmentioning
confidence: 99%
See 3 more Smart Citations